A neurofobia nos estudantes de medicina da UFRN: um estudo com métodos mistos - Lima, Guilherme Lucas de Oliveira (2019)
Background: The increasing prevalence of neurological diseases imposes the need to train physicians capable of providing initial care to this population. Feelings of inability to treat neurological patients and fear of neuromedicine (branch that studies neuroscience, neurology and neurosurgery) are present among students and physicians, from which the term “neurophobia” emerged at least 25 years ago. Objectives: To diagnose neurophobia, to understand its development in medical students at UFRN-Natal-RN and to propose transformative measures for mitigate this burden. Methods: A mixed-method explanatory study was conducted, into two phases: In quantitative phase, an electronic questionnaire was sent to all medical students to evaluate the perceptions about neuromedicine at 5-level Likert scale. The items dealt with the level of knowledge, confidence (in problem solving), interest, difficulty to learn and fear of neuromedicine, as well as its importance for generalist training. The neurophobic group represented students who assessed themselves with fear levels at 4 or 5. The weighted average of the Likert items showed trends: positive (>4), neutral (between 3-4), and negative (<3), except for difficulty and fear. The descriptive and comparative statistical analysis of the groups was performed according to the variable categories, allowing associations of the factors involved in neurophobia, with a significance level of p <0.05. In qualitative phase, a Focus Group (8 students) and 5 interviews were made in order to achieve saturation. The transcription of both allowed categorical thematic content analysis according to Bardin-Minayo. The triangulation of the methods was performed. Results: Two hundred and fifteen students answered the questionnaire. The overall prevalence of neurophobia was 41.9% (n = 90) showing growth during the course. The tendency was negative for the items knowledge, confidence and fear of neuromedicine and positive for the importance of neuromedicine for the general practitioner. The neurophobic group noticed greater difficulty, less knowledge, confidence and interest in neuromedicine than non-neurophobic group. The students' statements showed a preconceived view that may be associated with the student's immaturity, where both corroborate the negative perception of neuromedicine at the beginning of the course. Students also understood that neurophobia worsens throughout the course and is associated with the teaching format of neuromedicine: at the beginning, there is little clinical context, and throughout the course, they are exposed to specific content, a consequence of the specialty-centered curriculum model. The teacher as protagonist of greater curriculum integration, bringing more applicability to neuromedicine in the context of general education, were the students' proposals to combat neurophobia. Final considerations: This exploratory study, pioneer in the use of mixed methods (quantitative and qualitative), recognizes that neurophobia has a high prevalence among UFRN students and it has originated since the beginning of the course. Teacher development programs and a more integrated neuromedical curriculum focused on generalist training were the students' proposals to mitigate neurophobia.